Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. Defensive silence as a mediating variable Between Organizational Trust and Work Alienation " A Field Study on Aleppo Public Banking Sector"Mrs. Ayam Ibrhm Alabed2. The impact of administrative control on the performance of employees: An applied study on the Islamic insurance companyDr. Mutaz Mohamed Sorkaty , Dr. Ayman Sidahmed Mokhtar3. Medical tourism based on natural ingredients and health structures as one of the solutions to obilize economic resourcesCo-Prof. Slim Bourchid Abdelkader , Asst-Prof. Elsiddig Yousif Mohammed Mousa4. The reality of the implementation of national integrity standards in public sector by the council of common services of Irbid as perceived by the council staffDr. Sabrey Radi Ali Daradkah5. The Role of Administrative Performance in Customer Service in Achieving Satisfaction and Belonging to Commercial DealersA field study on the grain mills sector in SudanDr. Sara Suliman Alawad Mudwi, Dr. Reda Abdelfattah Ibrahim Mohamed6. The relationship between transformational leadership and entrepreneurial performance: A study on a sample of service sector institutions of Khartoum State 2022Dr. Hassan Abdelrahmim Fadul Mohamed , Co-Prof. Elsheikh Mohammed Elkhidir Mohammed, Dr. Anis Mohammed Souissi , Dr. Huthayfah Hadi Madkhali7. The Applying Islamic Financial Accounting Standards and Its role in Raising The Creditworthiness of Islamic Financial Institutions: A field Study on A sample of Sudanese BanksDr. Sondous Abdalaziz Alshami , Dr. Abdelrahim Mahgoub Ahmed Mohammed , Dr. Maha Mosa Mohammad Salama , Prof. Yasir Tajelssir Mohammed Sanad , Dr. Elhadi Mekki Mawan Somij8. Factors affecting saving in Sudan during the period 2008-2018Dr. Minas Abdelrahman Ali Alkhabir
Keywords: Journal of Economic, Administrative and Legal Sciences